DIAKON PEREMPUAN PADA PERIODE KRISTIANI AWAL - Edison R.L Tinambunan (Litbang STFT Widya Sasana Malang, 2011)
Deaconess is an actual topic in this present time, especially in relation to the feminist movement. This research presents a historical study on the existence of deaconesses in the first six centuries. The research uncovers various aspects of deaconess and reveals the reason behind the fact that deaconess does not exist in Latin Church. By contrast, the Oriental Church has maintained the existence of deaconesses up to the present time. Keywords: Diakon, Diakon Perempuan, Perempuan, Gender, Kristiani awal, Didaskalia, Konstitusi Para Rasul, Nicea, Kalcedon